1966
DOI: 10.1029/jz071i003p00785
|View full text |Cite
|
Sign up to set email alerts
|

Auroral electrojet activity indexAEand its universal time variations

Abstract: An index, denoted by AE, is derived as a measure of global electrojet activity. The basic data used are 2.5‐minute readings of the H trace in the standard magnetograms from seven auroral‐zone observatories. The readings are referenced to a level determined for each observatory from quiet intervals. All the data from the seven observatories are then plotted against UT, and two envelopes are drawn to embrace all the points. The index AE at any epoch is defined by the distance (or separation) between the upper an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
545
1
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 815 publications
(572 citation statements)
references
References 17 publications
2
545
1
8
Order By: Relevance
“…The AE index measures the auroral electrojet [Davis and Sugiura, 1966], and the Dst index measures variations in the ring current [Akasofu and Chapman, 1964]. Hamrin et al [2010] observed that plasma sheet energy conversion is influenced similarly by the geomagnetic activity as measured by variations in Kp and AE.…”
Section: Dependence On Magnetospheric Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…The AE index measures the auroral electrojet [Davis and Sugiura, 1966], and the Dst index measures variations in the ring current [Akasofu and Chapman, 1964]. Hamrin et al [2010] observed that plasma sheet energy conversion is influenced similarly by the geomagnetic activity as measured by variations in Kp and AE.…”
Section: Dependence On Magnetospheric Activitymentioning
confidence: 99%
“…Note that the AE index is designed to measure auroral activity by capturing the behavior of the auroral electrojet [Davis and Sugiura, 1966]. Hamrin et al [2010] showed that the occurrence frequency, as well as the power density strength, of both CLRs and CGRs increase during times of high AE [see Hamrin et al, 2010, Figures 3 and 6a].…”
Section: Explicit Relation To Auroral Activitymentioning
confidence: 99%
“…The auroral electrojet index (AE) developed by Davis and Sugiura [1966] is well correlated with the strength of the auroral electrojet currents in the Northern Hemisphere ionosphere and is traditionally employed as an indicator of the magnitude of global geomagnetic activity. The AE index is defined as the difference between the auroral electrojet upper (AU) and lower (AL) indices.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Another signature of substorm onset is the enhancement of geomagnetic activity as measured by the AL and AU geomagnetic indices, defined by Davis and Sugiura [1966]. During the substorm growth phase, enhanced plasma convection leads to an observed gradual increase in both the AL and the AU indices [McPherron, 1970].…”
Section: Introductionmentioning
confidence: 99%